Proceedings of the 27th ACM SIGSPATIAL International Conference on Advances in Geographic Information Systems 2019
DOI: 10.1145/3347146.3359095
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Find Hydrological Corrections

Abstract: High resolution Digital Elevation models, such as the (Big) grid terrain model of Denmark with more than 200 billion measurements, is a basic requirement for water flow modelling and flood risk analysis. However, a large number of modifications often need to be made to even very accurate terrain models, such as the Danish model, before they can be used in realistic flow modeling. These modifications include removal of bridges, which otherwise will act as dams in flow modeling, and inclusion of culverts that tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Mao et al (2016) showed that the use of skip connections helps the training process to converge much faster and attain a higher-quality local optimum. So far, U-Net and its variants have been used in a large number of DL applications in geosciences (Sun, 2018;Arge et al, 2019;Karimpouli and Tahmasebi, 2019;Mo et al, 2019;Zhong et al, 2019;Zhu et al, 2019).…”
Section: Attention-based Deep Convolutional Neural Netmentioning
confidence: 99%
“…Mao et al (2016) showed that the use of skip connections helps the training process to converge much faster and attain a higher-quality local optimum. So far, U-Net and its variants have been used in a large number of DL applications in geosciences (Sun, 2018;Arge et al, 2019;Karimpouli and Tahmasebi, 2019;Mo et al, 2019;Zhong et al, 2019;Zhu et al, 2019).…”
Section: Attention-based Deep Convolutional Neural Netmentioning
confidence: 99%
“…Further details are given in Section 4. To be able to handle arbitrarily sized and shaped regions with the U-Net model, we follow the construction from [1] that handles this exact problem. In short, we cover the given input region with fixed size overlapping rectangles, called tiles, matching the expected input size for the U-Net, and use the U-Net model to compute the probability of fortification for each cell in each tile.…”
Section: Applying U-net and Handling Arbitrarily Sized Regionsmentioning
confidence: 99%
“…For this computation the weights depend on the position in the covering tile: The closer to the center of the tile the cell is (more context) the higher the weight and the closer to the boundary the less weight. For a full description of this algorithm we refer to [1]. Figure 5 shows an example where this algorithm combined with our U-Net has been applied to a large area.…”
Section: Applying U-net and Handling Arbitrarily Sized Regionsmentioning
confidence: 99%